Manajemen Kurikulum Pendidikan Islam - Abul Mafaakhir; Slamet Untung (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The aim of writing this work is to try to describe and analyze the concept of Islamic education curriculum management. In literature review research on Islamic education curriculum management, the first step is to identify relevant theoretical sources, including books, journal articles and official documents. Data sources include scientific literature, documents related to management, as well as interviews with Islamic education experts and management practitioners. Data collection techniques include online literature searches, document studies, and interviews, while data analysis can be carried out qualitatively or descriptively. The result of this work is that the curriculum as a plan for all activities that support the achievement of educational goals still has an important role, at least in coloring the personality of students. Starting from covering educational curriculum management which plays a role, especially in Islamic education curriculum management. Islamic curriculum management plays a very important role in determining the success or failure of implementation and whether the curriculum is good or bad, which will influence educational outcomes. Curriculum management is related to planning, implementation, and evaluation or control of the curriculum. If you can see it as a whole, educators (teachers) will be able to understand to what extent the curriculum is able to build critical awareness of students or even not at all. Therefore, it is very necessary to understand the management of the Islamic education curriculum textually and contextually so that educators can apply the curriculum in learning, especially in learning Islamic Religious Education in educational institutions.